2020
DOI: 10.1096/fj.202000782
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme 2 in severe acute respiratory syndrome coronavirus and SARS‐CoV‐2: A double‐edged sword?

Abstract: Human angiotensin‐converting enzyme 2 (ACE2) facilitates cellular entry of severe acute respiratory syndrome coronavirus (SARS‐CoV) and SARS‐CoV‐2 as their common receptor. During infection, ACE2‐expressing tissues become direct targets, resulting in serious pathological changes and progressive multiple organ failure or even death in severe cases. However, as an essential component of renin‐angiotensin system (RAS), ACE2 confers protective effects in physiological circumstance, including maintaining cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 51 publications
1
109
0
8
Order By: Relevance
“…On the other hand, several studies suggest that ACE2 has an anti-inflammatory and protective effect, especially on the respiratory system, by changing angiotensin II to angiotensin (1-7). In this view, the administration of ACEIs/ARBs could help the respiratory system to respond more efficiently to the infection with SARS-CoV2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies suggest that ACE2 has an anti-inflammatory and protective effect, especially on the respiratory system, by changing angiotensin II to angiotensin (1-7). In this view, the administration of ACEIs/ARBs could help the respiratory system to respond more efficiently to the infection with SARS-CoV2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The ACE2 receptor is expressed in the type II pneumocytes of the lungs and also in other tissues, including the heart, tubular epithelial cells in kidneys, testis, adipose tissue, and the enterocytes in the gastrointestinal tract and vascular endothelial cells ( 119 ). A recent study evaluated ACE2 expression in older men and women with heart failure and found in two independent cohorts that circulating plasma concentrations of ACE2 were higher in men than in women ( 120 ).…”
Section: Immune Responsementioning
confidence: 99%
“…The unique SARS-CoV-2 characteristics and its unprecedented mechanisms of actions challenge the precise description of its mechanisms of actions and pathogenicity [10][11][12][13][14][15]. The only aspect of SARS-CoV-2 that has demonstrated undisputed characterization is its cell entry, which has shown to be dependent on angiotensinconverting enzyme-2 (ACE2) receptor and transmembrane serine protease 2 (TMPRSS2).…”
Section: Introductionmentioning
confidence: 99%